Roughness and hardness optimization of 12L-14 steel using the response surface methodology - Arenas, Wilson (2019)
This research used the response surface technique to optimize 12L-14 steel hardness and roughness based on the austenitizing time and temperature. The multi-objective problem was managed by scaling the desirability and weighting function using the analytical hierarchical process (AHP). The results show that the maximum hardness is obtained at 846.9 °C for 48.61 minutes.